Biologia de Liriomyza sativae Blanchard, 1938 (Diptera: Agromyzidae) em tomateiros submetidos à aplicação de silício - Barros, Adamastor Pereira (2016)
Tomato is sensitive to attack the leafminer fly, Liriomyza sativae.The injuries caused by the leafminer compromise the health of the plant, once both the punctures as for feedingas galleries made by larvaes favoring the entry of pathogens and reduce the p